PENGARUH PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KREATIF MAHASISWA PADA MATA KULIAH PENGEMBANGAN MEDIA DAN SUMBER BELAJAR UMUSLIM BIREUEN - Lissa Zikriana; Novi Sari Liani; Desy Sary Ayunda; Sharfina (Jurnal Bionatural, 2024)
This study aims to determine whether the Project Based Learning learning model has an effect on the thinking skills of students of the Umuslim Bireuen Elementary School Teacher Training Program. The formulation of the problem is whether the Project Based Learning learning model has an effect on the thinking skills of students of the Umuslim Bireuen Elementary School Teacher Training Program. The research method used is an experimental method with a sample size of 120 people with 60 people in the control class and 60 people in the experimental class. Data analysis was carried out using the independent sample t-test. The results of the study showed a sig.0.05>0.452 value so that it can be concluded that there is an influence of the Project Based Learning learning model on students' thinking skills.